Peningkatan Kualitas Hidup Lansia pada Masa Normal Baru dengan Pelatihan Terapi Aliran Saliva dengan Senam Wajah dan Pembuatan Olahan Nanas - Wahyu Jati Dyah Utami; Yuniarti Yuniarti; yodong yodong; Miranda Gita Wahyuningtyas (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2023)
As we get older, the function of the body's organs will decrease (organ degeneration), both due to natural factors and due to disease. An estimated 30% of the elderly aged 65 years and older have decreased salivary production. This situation is caused by atrophy in the salivary glands (saliva) which will reduce saliva production and change its composition. Decreased salivary secretion will cause discomfort in the oral cavity, pain, an increase in the level of dental caries and oral infections. Facial gymnastics is the act of giving massage to the facial area from top to bottom around the cheeks, mouth and chin, this activity can stimulate salivary secretion and oral cavity function, from the results of research (Medina, 2018) facial gymnastics can increase the speed of salivary flow. In addition to facial exercises, salivary flow can also be stimulated by pineapple consumption. Pineapple proved effective in inducing saliva production is pineapple citric acid content in pineapple fruit can stimulate existing salivary glands, namely parotid, submandibularis, sublingualis and additional glands. The results of community service showed. The elderly's knowledge about saliva production has increased and followed by an improvement in quality of life. This is because facial gymnastics activities are carried out regularly for 21 days. Activities that are carried out repeatedly will become a conditioning and habit. Furthermore, there is a learning process, namely the transformation of input / input then reduced, elaborated and then stored in the memory of Notoatmojo (2012).